Copper Contamination Levels and Storage-Related Migration in Commercial Canned Fruit Cocktail Products Using AAS and Dithizone Screening - Muhammad Faris Adrianto; Sudjarwo; Khanaya Angelie; Luvena Navelyn Anggi Putri (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Heavy metal contamination in food has become a growing health concern due to its toxic and accumulative effects, particularly from metals such as copper (Cu). Canned fruit products, especially those containing acidic components, are vulnerable to metal leaching from packaging. Objective: This study aimed to determine the levels of copper contamination in commercially available canned fruit cocktail products and evaluated temporal changes in Cu levels during 12 weeks of room-temperature storage. Additional qualitative screening using dithizone-impregnated strips was assessed for detecting Cu presence. Methods: A total of 12 samples from four different brands were analyzed using Atomic Absorption Spectrophotometry (AAS) to quantify copper concentrations at two-week intervals. Results: Initial copper concentrations ranged from 0.09 to 1.47 ppm, all of which were below the FAO/WHO permissible limit of 2 ppm for processed foods, although several samples approached the upper threshold. After 12 weeks, Cu levels increased progressively during storage, confirmed statistically by repeated-measures ANOVA (p < 0.05). The dithizone strip test confirmed copper presence through visible color changes. Conclusion: The study confirmed that copper contamination in canned fruit cocktail products increased with storage time, potentially exceeding safety limits.